Distinct phenotypes of patients and healthcare resource utilization after hospitalization for COVID-19: an observational study - Claire Marant Micallef; Manon Belhassen; Florence Ader; Valeria Martinez; Eric Van Ganse; Marjorie Bérard; Mélanie Née; Mikhail Dziadzko; Frédéric Aubrun (BMC Health Services Research)
Abstract Background Little is known about postdischarge healthcare resource use (HCU) among patients hospitalized for coronavirus disease 2019 (COVID-19). The objective was to identify distinct profiles of patients based on postdischarge cares. Methods This was a retrospective cohort study using the French National Health System claims database. We followed up all patients hospitalized for COVID-19 between 2020/02/01 and 2020/06/30 for 6 months; the discharge date was the index date. We excluded patients who died during the index stay or within 30 days after discharge. We described patients’ HCU over 5 months from day 31 after the index date to the end of follow-up, i.e., the post-COVID-19 period. We described the sociodemographic and clinical characteristics of the participants and 44 selected types of HCU, including medical and emergency room visits, medications, medical and biological tests, oxygen therapy, rehabilitation, rehospitalization, nurse visits, and sick leave. We performed Ward’s ascendant hierarchical clustering (AHC) analysis to identify groups of patients with similar post-COVID-19 HCU and described HCU and clinical characteristics by cluster. Results The study population included 68,822 patients (median age: 64.8 years, 47% women). Eight clusters of patients were identified, each comprising between 1,163 and 35,501 patients. Four clusters were characterized by older patients and high proportions of comorbidities, i.e. cancer (cluster 3), mental disorders (cluster 4), cardiac insufficiency (cluster 5) and respiratory failure (cluster 6). Cluster 8 was characterized by younger patients, often obese and with low mortality. Another cluster was characterized by complex index stays (cluster 7) and a last cluster (cluster 2) by specific medical contacts and therapy. The main cluster (cluster 1, n = 35,501) was similar to the overall study population. The duration and complexity of the index stay also varied across clusters. Conclusions Based on HCU data, AHC identified 8 clinically relevant profiles of patients surviving the acute episode of COVID-19 hospitalization. The clusters illustrate the many impacts of COVID on the health status of infected patients and may help anticipate future needs of care in a similar context.